Genome-wide identification, in-silico characterization, and expression analysis of polygalacturonases in different fungal species - Laiba Amin; Imran Zafar; Adil Jamal; Syed M. Safeer Mehdi Bokhari; Fayez Saeed Bahwerth; Muhammad Noman (Molecular Genetics and Genomics, 2026)

Self-assembled zein-chitosan-salicylic acid nanoemulsions delay mango senescence by modulating hormone signaling and redox-related transcriptional networks - Yiting Fan; Muhammad Adil; Jiahao Ren; Youning Zou; Tai Boon Tan; Chin Ping Tan; Fengsong Liu; Xinglong Xiao (Food Hydrocolloids, 2026)

Facile synthesis of cobalt-iron layered double hydroxide and its derived mixed metal oxide for Congo red and Pb(II) remediation - Ramzan Akhtar; Adil Khan; Maria Gul; Mohsin Ali Raza Anjum; Iqra Rafique; Muhammad Rehan; Rashid Nazir Qureshi; Sajid Iqbal; Muhammad Saifullah (Colloids and Surfaces C: Environmental Aspects, 2026)

Identification and functional verification of resistance genes against Lily bulb virus-1 (LbV-1) in Lilium: Insight from sRNA sequencing and transcriptomic profiling - Nisar Uddin; Xia Li; Noor Muhammad; Muhammad Shahid; Adil Hussain; Lili Zhang; Daochen Zhu (Plant Science, 2026)

Improving blasting productivity in underground mining using non-Newtonian fluid stemming: A field study - Bunyamin Kahraman; Derek B. Apel; Muhammad Adil; Coralee Heske; Matthew Violot (International Journal of Rock Mechanics and Mining Sciences, 2026)

Recent advances in spore-killing technologies: A comprehensive review on killing effect, mechanism and application in food matrices - Chenghao Li; Jiahao Ren; Muhammad Adil; Yiting Fan; Youning Zou; Xinglong Xiao (Food Microbiology, 2026)

Performance analysis of a helium-nitrogen binary gas mixture centrifugal compressor for terrestrial gas-cooled reactor power plants of closed Brayton cycles - Arif Aziz; Qun Zheng; Adil Malik; Muhammad Haris; Ghulam Ishaque; Shadman Ahmad Khattak (Annals of Nuclear Energy, 2026)

Machine learning–enhanced framework of complex nonlinear wave dynamics in oceanic atmosphere - Muhammad Qasim; Muhammad Zafarullah Baber; Yakup Yildirim; Adil Jhangeer; Muhammad Waqas Yasin (Ocean Engineering, 2026)

AI and Multi-Omics for Climate-Resilient Remediation of Heavy Metal Soil Toxicity - Isma Gul; Muhammad Adil; Siqi Lu; Safdar Bashir; Heli Lu; Muhammad Daud; Younas Iqbal; Yu Tao (Water, Air, & Soil Pollution, 2026)

Mapping Flood Co-Adaptation Strategies in a Vulnerable River Basin: Engaging Youth in Collaborative Decision-Making - Zulfaqar Sa’adi; Zainura Zainon Noor; Nur Syamimi Zaidi; Ee Ling Yong; Fateha Abdul Razak; Nurul Hana Mohamed; Zainab Mat Lazim; Ainul Syarmimi Rosli; Mohd Faiz Foze; Siti Hanna Elias; Khairunnisa Abdul Halim; Muhammad Burhanuddin Bahrodin; et al. (Environmental Management, 2026)

Effect of increasing temperatures on duckweed growth, photosynthetic performance and frond ontogenesis - Muhammad Irfan; Muhammad Adil Chaudhry; Manuela Bog; Sándor Szabó; Ilona Mészáros; Marcel A. K. Jansen; Viktor Oláh (Plant Cell Reports, 2026)
Key message Duckweeds offer a suitable platform to study the effects of elevated temperatures on aquatic plants, and chlorophyll fluorescence imaging can reveal frond-level distribution of temperature stress. Abstract Temperature rise associated with climate change poses a major challenge for aquatic plants. It has a strong influence on their physiological performance and, consequently, their competitive ability and fitness. Yet comparative studies of impacts on different species remain scarce. This study investigated the effects of four different temperature regimes between 20 and 35 °C on five duckweed species ( Spirodela polyrhiza , Landoltia punctata , Lemna gibba , Lemna minor and Lemna minuta ) by integrating growth- and photosynthesis-based parameters. We also recorded spatial patterns of photosystem II efficiency within fronds using chlorophyll a fluorescence imaging to understand how temperature stress is distributed throughout the frond development. The results highlighted substantial inter-specific variation in thermal responses and underscore the importance of integrating physiological and growth-based indicators to predict aquatic plants’ responses to climatic warming. Through simultaneous measurement of growth performance, photosynthetic efficiency and within-frond heterogeneity, this study provides mechanistic insights into how rising temperatures may influence duckweeds. Such knowledge is essential for predicting future shifts in freshwater primary productivity, species dominance, biological invasions and ecosystem stability under the current global warming scenario.

Mitogenomic Architecture and Phylogenetic Insights Shed Light on the Matrilineal Evolution of the Mahseer Fish Neolissochilus sumatranus (Cyprinidae: Torinae) in Southeast Asia - Sekar Larashati; Angkasa Putra; Sarifah Aini; Gema Wahyudewantoro; Mey Ristanti Widoretno; Dwi Febrianti; Huria Marnis; Imam Civi Cartealy; Tri Widiyanto; Ruby Vidia Kusumah; Anik Budhi Dharmayanthi; Muhammad Hilman Fu’adil Amin; et al. (Biochemical Genetics, 2026)

Long-Term Fermented Chicken Manure (CM) Amendment Enhances Soil Health, Sugar Beet Yield, and Shifts Microbial Functional Diversity - Jianyu Zhang; Songlin Yang; Xiaochen Lin; Shafaque Sehar; Muhammad Ishfaq; Muhammad Riaz; Muhammad Faheem Adil; Saqib Bilal; Xiaoyu Zhao; Jean Wan Hong Yong; Baiquan Song (Sugar Tech, 2026)

Modeling fractional wave propagation in ocean engineering: Neural network solutions for the clannish random walker’s parabolic equation - Muhammad Qasim; Fengping Yao; Muhammad Zafarullah Baber; Adil Jhangeer (Ocean Engineering, 2026)

Volcanism-induced algal blooms in the Ediacaran Salt Range Formation, Pakistan - Imran Khan; Jingqiang Tan; Qingyong Luo; Lipeng Yao; Muhammad Jamil; Adil Khan (Global and Planetary Change, 2026)

Formulation and Evaluation of Losartan Potassium Microparticles Loaded Controlled-Release Tablets: An In-Vitro Perspective - Kamran Ahmad Khan; Ashfaq Ahmad; Muhammad Israr; Saima Mahmood; Farman Shah; Naveed Ullah; Fida Muhammad; Anam Adil; Sami ul Haq; Haroon Khan (Journal of Pharmaceutical Innovation, 2026)

Exploiting the biocontrol potential of Chaetomium globosum against Fusarium solani root rot in wheat: climate-responsive phytohormonal regulation, genetic diversity, and sustainable management - Marwa S. Fouad; Khaled M. A. Ramadan; Hisham A. Mohamed; Mohamed Abou-Zeid; Shafik D. Ibrahim; Muhammad Munir; Eslam S. A. Bendary; Mohamed M. Aboul Fotouh; Sallah A. Al Hashedi; Adil AlShoaibi; Zafar Iqbal; Ahmed M. Ismail; et al. (European Journal of Plant Pathology, 2026)

Evaluation of the antiulcer activity of methanolic extract of Bidens biternata on experimental rats via involvement of the PGE2/Nrf2/HO-1/NF-κB/Caspase-3 pathways - Muhammad Murtaza; Mohammad Khalid; Gaurav Gupta; Haider Ali; Kavita Goyal; Adil Abalkhail; Fahad M. Aldakheel; Farhan R. Khan; Ameeduzzafar Zafar (South African Journal of Botany, 2026)

Fintech-driven sustainability: Examining the pathways to sustainable performance through innovation and circular practices in emerging market SMEs - Muhammad Waqar; Adil Riaz; Jibal Baig; Zahid Bashir; Zhonghua Cai (Journal of Cleaner Production, 2026)

Unlocking ketone dimerization efficiency with multifunctional Zr and Hf based UiO-66 and NUS-6 MOFs: A synergy of experiment and theory - Muhammad Kashif Majeed; Rashid Iqbal; M.Umar Majeed; Muhammad Akram; M.Zeeshan Ashfaq; Adil Saleem (Fuel, 2026)

Nanotechnology for Climate-Resilient Agriculture: Advancing Water Efficiency, Crop Resilience, and Sustainable Food Security - Muhammad Adil; Isma Gul; Siqi Lu; Heli Lu; Yu Tao (Water, Air, & Soil Pollution, 2026)

Ghost-rock karstification and cave system modelling in the Middle Atlas, Morocco - Iliass Naouadir; Salih Muhammad Awadh; Samira Adil; Mohammed Ettaki; El Hassane Chellai; Abdallah Elaaraj; Abdennabi Alitane; Antonio Pulido Bosch; Zaher Mundher Yaseen (Modeling Earth Systems and Environment, 2026)

Fabrication, Preparation and In-Vitro and In-Vivo Evaluation of Metoprolol Tartrate Controlled-Release Matrices to Establish a Correlation - Kamran Ahmad Khan; Ashfaq Ahmad; Muhammad Israr; Saima Mahmood; Sami-ul-Huq; Naveed Ullah; Anam Adil; Fida Muhammad (Journal of Pharmaceutical Innovation, 2026)

Decoding the catalytic potential of a Cycloclasticus zancles ring-hydroxylating dioxygenase through computational analysis for enhanced PAH biodegradation - Muhammad Naveed; Ahmed Raza; Ahiba Adil; Abubakar Majeed; Sana Miraj Khan; Ayaz Ali Khan; Rania Ali El Hadi Mohamed; Nawal H. Siddig; Hayam A. Alwabsi; Hanan Abdulrahman Sagini (Biodegradation, 2026)

Antibiotic resistance pattern and molecular study of foodborne pathogenic bacteria isolated from Poultry meat in Bangladesh - Shahin Mahmud; Muhammad Wasim; Md. Firoz Ali; Md. Omar Faruque; Sourav Sarker; Md. Rayhan Ali; Ashraf Hossain Talukder; A.K.M. Mohiuddin; Somaresh Kumar Mondal; Shah Adil Ishtiyaq Ahmad (Food and Humanity, 2026)

Molecular detection of Toxoplasma gondii in Amblyomma gervaisi ticks infesting monitor lizards (Varanus bengalensis) - Muhammad Naeem; Muhammad Ammar Ameen; Hafiza Misbah Munir; Huma Fatima; Shakir Ullah; Hira Muqaddas; Kasim Sakran Abass; Adil Khan; Furhan Iqbal (Experimental and Applied Acarology, 2026)

Myricetin as a potential therapeutic agent against Pseudomonas aeruginosa : inhibition of biofilm formation, quorum sensing, and virulence factor production - Sallah A. Al Hashedi; Saif M. Dmour; Hamad Sarheed Galut; Ayman Daifallah Ismail Alsheikh; Mohammad H. Abukhalil; Sham Ma’aitah; Najeeb S. Al-Zoreky; Khaled M.A. Ramadan; Muhammad Naeem Sattar; Zafar Iqbal; Adil Alshoaibi; Sultan A. M. Saghir (Biofouling, 2026)

CRISPR-Cas9 and next-generation gene editing strategies for therapeutic intervention of neurodegenerative pathways in Alzheimer’s disease: a state-of-the-art review - Muhammad Sohail Khan; Imran Zafar; Adil Jamal; Fayez Saeed Bahwerth; Samiullah Khan; Muhammad Faizan; Hanif Khan; Muhammad Noman; Kendrix Okeibunor; Ashfaq Ahmad; Muhammad Zain Ul Abedin (Acta Neurologica Belgica, 2026)

Omics-driven soil bioremediation of emerging contaminants: Integrating sensors, digital twins, and microbial biotechnology - Asad Shah; Mohammad Nauman Khan; Waqar Ali; Muhammad Numan Khan; Hidayat Ullah; Zahra Barati; Adil Farooq Lodhi; Lixiao Nie (Applied Soil Ecology, 2026)

Long term dynamics and drivers of bioavailable silicon from source to sink in Taihu Watershed, China - Tao Yu; Yixiang Deng; Adil Muhammad; Zhen Huang; Gaoying Xu; Chengda He (Journal of Environmental Sciences, 2026)

Climatic and tectono-geomorphological controls on karst spring dynamics: Case study of the El Menzel Causse, Middle Atlas (Morocco) - Iliass Naouadir; Marzieh Khalili; Salih Muhammad Awadh; Samira Adil; El Hassane Chellai; Mohammed Ettaki; Abdennabi Alitane; Abdallah Elaaraj; Zaher Mundher Yaseen (Journal of African Earth Sciences, 2026)

Agricultural and socio-ecological benefits of reducing chemical nitrogen fertilizer and using organic amendments: a sugar beet case study in China's black soil region - Yunlong Guo; Xiaochen Lin; Muhammad Faheem Adil; Muhammad Ishfaq; Muhammad Riaz; Shafaque Sehar; Songlin Yang; Yan Wang; Zhishan Yan; Baiquan Song (Applied Soil Ecology, 2026)

Fermentation-based valorization of agro-industrial cereal wastes and by-products - Muhammad Zeeshan Adil; Sebahat Oztekin; Afifa Aziz; Deniz Gunal-Koroglu; Esra Capanoglu; Andres Moreno; Waseem Khalid; Tuba Esatbeyoglu (Trends in Food Science & Technology, 2026)

Greener hydrogen production and storage revolution towards a low-carbon future: an overview of current scenarios and future prospects - Tahir Rasheed; Sameera Shafi; Muhammad Tuoqeer Anwar; Hifsa Khurshid; Ahmad Naveed; Adil Alshoaibi; Nisrin Alnaim; Yunjian Liu; Tauqir A. Sherazi (Fuel, 2026)

Exosomal CeRNAs from the tumor microenvironment: hidden drivers of colorectal cancer progression - Faris Anad Muhammad; Abdulkareem Shareef; S. Renuka Jyothi; Priya Priyadarshini Nayak; J. Bethanney Janney; Gurjant Singh; Aashna Sinha; Nodira Rabbimova; Hayder Naji Sameer; Ahmed Yaseen; Rasim M. Salih; Mohaned Adil (Journal of Molecular Histology, 2026)

Mitogenomic Characterization and Phylogenetic Insights of the Ornamental Sail-Fin Molly (Poecilia velifera) in Non-Native Indonesian Waters - Sarifah Aini; Rina; Sinar Pagi Sektiana; Soo Rin Lee; Ah Ran Kim; Hye-Eun Kang; Muhammad Hilman Fu’adil Amin; Won-Kyo Jung; Angkasa Putra; I Nyoman Suyasa; Shantanu Kundu; Hyun-Woo Kim (Biochemical Genetics, 2026)

Unveiling Hidden Threats: Molecular Detection and Genetic Diversity of Hepatozoon spp. and Toxoplasma Gondii in Wild Rodents of Saudi Arabia and Their Ectoparasites - Maryam Ijaz; Samia Q. Alghamdi; Abdullah D Alanazi; Mubashra Salim; Muhammad Naeem; Muhammad Ali; Shabana Mukhtiar; Kasim Sakran Abass; Hira Muqaddas; Adil Khan; Furhan Iqbal (Acta Parasitologica, 2026)

Neuro-computational surrogates for aqueous fractional-order nekton-plankton spatiotemporal dynamics under toxicant stress, refuge efficacy, and nutrient flux modulation - Adil Sultan; Chuan-Yu Chang; Muhammad Junaid Ali Asif Raja; Adiqa Kausar Kiani; Muhammad Shoaib; Muhammad Asif Zahoor Raja (Water Research, 2026)

Mitigating cadmium toxicity in rice through tandem application of zinc oxide nanoparticles and Serendipita indica as revealed by multi-omics and NMT-based ion flux analysis - Muhammad Faheem Adil; Muhammd Naeem; Shafaque Sehar; Fanrui Zhou; Syed Muhammad Hassan Askri; Yunqi Liu; Zhong-Hua Chen; Wenwu Zhou; Imran Haider Shamsi (Journal of Hazardous Materials, 2026)

Rational synthesis for harnessing dual-phase synergy in sulfide-oxide composite for high-performance supercapacitors - Adil Emin; Tursunay Mamitimin; Afei Ding; Anand Parkash; Muhammad Ahsan Farooq Qaisar; Inaam Ullah; Salamat Ali; Li Wang; Qiang Li (Chemical Engineering Journal, 2026)

Exopolysaccharides Enhance Wheat Tolerance to Combined Salinity and Nickel Stress by Modulating Growth and Antioxidant Defense - Nabil Touzout; Meriem Babaali; Mahfoud Ainas; Aftab Jamal; Adil Mihoub; Iftikhar Ahmad; Subhan Danish; Muhammad Farhan Saeed; Árpád Székely (Journal of Plant Growth Regulation, 2026)

Orange peel derived biochar assisted rGO@MoS₂ composite for visible light driven ciprofloxacin degradation and hydrogen evolution - Asim Jilani; Mohsin Raza Dustgeer; Mohammad Omaish Ansari; Alishbah Zaka; Muhammad Adil Mansoor; Ammar A. Melaibari; Hussameldin Ibrahim (Journal of Water Process Engineering, 2025)

Physicochemical, Organoleptic and anti-obesity effects of water melon peel powder incorporation into chapatti - Sania Niaz; Samreen Ahsan; Muhammad Farhan Jahangir Chughtai; Tariq Mehmood; Muhammad Adil Farooq; Madiha Wali; Adnan Khaliq (Food and Humanity, 2025)

Advances in Microbial Bioremediation of Microplastics in Mangrove Sediments: a Comprehensive Review - Muhammad Sheeraz Javed; Muhammad Adil; Jiliang Zhang; Isma Gul; Muhammad Rauf; Saeed Ahmad; Bushra Moon; Siqi Lu; Heli Lu; Ali Haidar Gormani; Younas Iqbal; Hassan Mahmood (Water, Air, & Soil Pollution, 2025)

Growth, Yield, and Oil Quality of Sesame (Sesamum indicum L.) Cultivars Under Varying Row Spacings and Biofertilizer Application - Saddam Hussain; Abdul Qayyum; Amanullah Jan; Muhammad Ilyas; Izaz Ahmad; Uzair Ahmed; Emanuele Radicetti; Adil Mihoub; Aftab Jamal; Yaser Hassan Dewir (International Journal of Plant Production, 2025)

Macrophage migration inhibitory factor (MIF): a Janus-faced cytokine in viral pathogenesis and host defense - Mohamed J. Saadh; Faris Anad Muhammad; Abdulkareem Shareef; S. Renuka Jyothi; Priya Priyadarshini Nayak; Ashish Singh Chauhan; Siya Singla; Farida Khasanjanova; Hayder Naji Sameer; Ahmed Yaseen; Zainab H. Athab; Mohaned Adil (Immunologic Research, 2025)

Predictive analysis of plankton population dynamics in marine biosphere: a nonlinear ARX neural network for the carbon-thermal-nutrient-plankton asymmetric multifactor system for global warming - Adil Sultan; Muhammad Junaid Ali Asif Raja; Chuan-Yu Chang; Chi-Min Shu; Adiqa Kausar Kiani; Muhammad Shoaib; Muhammad Asif Zahoor Raja (Environmental Monitoring and Assessment, 2025)

Predictive modelling of radon variations in time series using wavelets, multiple linear regression and ARIMA - Nadeem Bashir; Awais Rasheed; Muhammad Osama; Adil Aslam Mir; Muhammad Rafique; Saeed Ur Rahman; Dimitrios Nikolopoulos; Muhammad Abdul Basit; Aftab Alam; Aleem Dad Khan Tareen; Kimberlee Jane Kearfott (Isotopes in Environmental and Health Studies, 2025)

Long-term impacts of agronomic practices on winter wheat yield, water use efficiency, and nitrogen use efficiency in global dryland regions: A meta-analysis - Muhammad Adil; Zhenchuang Wang; Yi Chen; Heli Lu; Siqi Lu; Safdar Bashir; Isma Gul; Huan Li; Zongran Han; Wanfu Feng (Soil and Tillage Research, 2025)

Low frequency electrostatic wave dynamics in the subsolar magnetosheath of Venus: A theoretical framework with multi-ion and suprathermal electrons - Adil Murad; Muhammad Adnan; Shahida Parveen; Ikramullah; Fida Younus Khattak (Planetary and Space Science, 2025)

Deciphering the role of non-covalent interactions in CO2 Capture: A DFT and COSMO-RS study of amino acid-based ionic liquids - Hira Karim; Sabahat Sardar; Suhan Prasantha Panditharatne; Asad Mumtaz; Muhammad Arfan; Azhar Mahmood; Jean-Marc Leveque; Syed Farooq Adil; Mohammad Rafe Hatshan; Mujeeb Khan (Journal of Environmental Management, 2025)

Surface engineering of single-crystal NCM811 with graphene for enhanced mechanical integrity - Muhammad Fasehullah; Sidra Jamil; Ghulam Ali; Keun Hwa Chae; Bushra Jabar; Adil Mansoor; Chao Tang (Chemical Engineering Journal, 2025)

Assessing Heavy Metal Contamination and Health Risks in Urban Street Dust: Insights from Pakistan's Industrial Growth - Ahsan Riaz Khan; Adil Mihoub; Aftab Jamal; Muhammad Farhan Saeed; Somayeh Soltani-Gerdefaramarzi; Muhammad Irfan Ahamad (Water, Air, & Soil Pollution, 2025)

Bacillus Inoculation Along with Biogas Slurry Mitigates Nickel Stress in Raphanus Sativus by Regulating Ni Accumulation and the Antioxidant Defense System - Iftikhar Ahmad; Shehzad Mehmood; Muhammad Atif Muneer; Aftab Jamal; Amjad Farooq; Muhammad Farhan Saeed; Qasim Ali; Umar Daraz; Nabil Touzout; Adil Mihoub; Jun Zhou (Water, Air, & Soil Pollution, 2025)

A Brief Outlook on the Preparation and Magnetic Properties of Iron Oxide Nanoparticles for Water Remediation - Younas Iqbal; Wencong Ma; Xuhui Li; Shenglei Fu; Asim Shahzad; Imtiaz Ahmad; Yangyang Wang; Muhammad Adil; Mohammad Abohashrh (Water, Air, & Soil Pollution, 2025)

Remarkable energy storage performance in lead-free tungsten bronze ferroelectrics for high temperature applications - Muhammad Fahad Riaz; Fayaz Hussain; Ali Dad Chandio; Zeshan Javed; Wenfeng Yue; Zhenhao Fan; Yuxiao Du; Bingsen Wang; Mohammad Abu Abdeen; Gulmurza Abdurakhmanov; Adil Alshoaibi; Yasemin Tabak; et al. (Chemical Engineering Journal, 2025)

Elucidating the Mitogenomic Blueprint of Pomadasys perotaei from the Eastern Atlantic: Characterization and Matrilineal Phylogenetic Insights into Haemulid Grunts (Teleostei: Lutjaniformes) - Arief Wujdi; Gyurim Bang; Muhammad Hilman Fu’adil Amin; Yeongju Jang; Hyun-Woo Kim; Shantanu Kundu (Biochemical Genetics, 2025)

Enhancing seismic activity classification in augmented soil gas radon time series data through computational intelligence techniques - Nadeem Bashir; Adil Aslam Mir; Muhammad Osama; Saba Maqsood Abbasi; Dimitrios Nikolopoulos; Shahzad Ahmad Qureshi; Muhammad Rafique (Journal of Atmospheric and Solar-Terrestrial Physics, 2025)

MnFe2O4 thin film electrodes via AACVD: A facile route for enhanced oxygen evolution reaction - Alishbah Zaka; Misha Aftab; Nudrat Fatima; Khola Mashood; Muhammad Adeel Asghar; Arshid Numan; Muhammad Sheraz Ahmad; Ali Haider; Mudassir Iqbal; Waqas Ali Shah; Muhammad Adil Mansoor (Fuel, 2025)

Polymeric carbon nitride-based semiconductors as a beneficial candidate in photocatalysis diversity: A comprehensive review - Sidra Tul Muntaha; Jawad Ali Shah Syed; Muhammad Mateen; Muhammad Ali Shahzad; Anand Parkash; Aqsa Asrar; Adil Emin; Ghulam Abbas Ashraf; Inaam Ullah; Muhammad Ahsan Farooq Qaisar; Salamat Ali; Ahmed Mahmoud Idris (Chemical Engineering Journal, 2025)

Prediction of compressive strength of stone dust-based fly ash bricks: experimental study and advanced machine learning algorithm - Mehtab Alam; Adil Khan; Muhammad Umar; Tauqir Ahmed; Ahmad Yar Mazari; Muhammad Usman Arshad (Innovative Infrastructure Solutions, 2025)

Effect of Different Levels of Copper Oxide (CuO) Nanoparticles and Biochar on Soil’s Microbial Activities and Maize (Zea Mays L.) Growth - Muhammad Abdullah Aziz; Sana Zahra; Bilal Adil; Amir Naserin; Muhammad Asad Hameed; Ijaz Ali; Temoor Ahmed; Ajaz Ahmad (Journal of Soil Science and Plant Nutrition, 2025)

Design of a fractional-order environmental toxin-plankton system in aquatic ecosystems: A novel machine predictive expedition with nonlinear autoregressive neuroarchitectures - Muhammad Junaid Ali Asif Raja; Adil Sultan; Chuan-Yu Chang; Chi-Min Shu; Muhammad Shoaib; Adiqa Kausar Kiani; Muhammad Asif Zahoor Raja (Water Research, 2025)

Mud volcanoes and microbial communities: Unraveling the mysteries of formation, features, and occurrence - Senthil Kumar Rajendran; Suprokash Koner; Bashir Hussain; Hsin-Chi Tsai; Zeng-Yei Hseu; Jung-Sheng Chen; Shih-Wei Huang; Danish Ali; Muhammad Adil Khan; Bing-Mu Hsu (Journal of Asian Earth Sciences, 2025)

Recent advancements in chemometrics based non-destructive analytical techniques for rapid detection of adulterants in milk and dairy products – A review - Rui Xu; Muhammad Zeeshan Adil; Sidra Jabeen; Khansa; Mahwish Tanveer; Sadia Younis; Bakhtawar Shafique; Long Li (Food Control, 2025)

Synergistic modulation of band structure and phonon transport for higher thermoelectric performance of WSe2 - Mazhar Hussain Danish; Amil Aligayev; Zahir Muhammad; Tao Chen; Adil Mansoor; Zia Ur Rahman; F.J. Dominguez-Gutierrez; Di Li; Jian Zhang; Zhuang-Hao Zheng; Xiaoying Qin (Chemical Engineering Journal, 2025)

Biopriming with Endophytes improves plant resilience to develop climate-smart, futuristic agricultural crops - Pragya Tiwari; Muhammad Adil; Kyeung-Il Park (World Journal of Microbiology and Biotechnology, 2025)

Foliar Application of Ascorbic Acid and α-Tocopherol Enhances Salinity Tolerance in Hordeum vulgare L. by Regulating Antioxidant Enzymatic Activity and Improving Physiological and Biochemical Responses - Sadaf; Sami Ullah; Sikandar Shah; Aftab Jamal; Adil Mihoub; Muhammad Farhan Saeed; Iftikhar Ahmad; Emanuele Radicetti; Adil Zia; Andrea Mastinu; Jakub Černý (Journal of Crop Health, 2025)
Soil salinity severely impairs crop productivity by disrupting physiological and biochemical processes. This study investigated the efficacy of foliar-applied ascorbic acid (AsA) and α‑tocopherol (α-toc) in enhancing salinity tolerance in barley ( Hordeum vulgare L. cv. AJJ). A pot experiment using a randomized complete block design with three replicates was conducted under controlled conditions. Seedlings at the 4–5 leaf stage were exposed to 0, 40, or 80 mM NaCl salinity stress, followed by foliar treatments of AsA and α‑toc (150 mg L⁻ 1 ). Germination, agronomic, physiological, and biochemical parameters were analyzed. Salinity stress at 40 and 80 mM NaCl significantly reduced germination percentage (GP) by 18.6% and 18.4%, respectively, compared to the control (86.6%). Foliar application of AsA + α-toc under 40 and 80 mM stress restored GP to 82.3% and 81.7%, reflecting recoveries of 16.8% and 15.6% overstressed groups. Water content in leaves, shoots, and roots declined by 10–30% under salinity but improved by 15–25% with AsA + α-toc. Photosynthetic pigments were severely affected: chlorophyll a and total chlorophyll content (TCC) decreased by 45.7% (1.75 to 0.95 mg g⁻ 1 FW) and 10.9% (1.75 to 1.56 mg g⁻ 1 FW) at 40 and 80 mM NaCl, respectively. AsA + α-toc mitigated these losses, elevating TCC by 42.6% under 80 mM stress. Soluble protein content increased by 186% (0.50 to 1.43 mg g⁻ 1 ) under 80 mM stress but was stabilized by antioxidant treatments. Antioxidant enzymes, including superoxide dismutase (SOD) and peroxidase (POD), surged by 40–60% under salinity, while AsA + α-toc reduced hydrogen peroxide (H 2 O 2 ) and malondialdehyde (MDA) levels by 30–50%. The combined application of AsA and α‑toc proved most effective, enhancing stress tolerance through improved osmotic regulation, antioxidant defense, and chlorophyll preservation. These findings highlight the potential of AsA and α‑toc as sustainable agronomic tools for cultivating barley in saline soils, with AsA showing marginally greater efficacy. Further field studies are warranted to validate these results under different climatic conditions.

Platelet-Rich Plasma (PRP) Mitigates Kidney Dysfunction in Alloxan-Induced Diabetic Mice via Modulation of Renal Iron Regulatory Genes - Humaira Allay Ali; Muddasir Hassan Abbasi; Tasleem Akhtar; Amin Arif; Mehreen Anjum; Sana Fatima; Rabia Mehmood; Adil Farooq; Nadeem Sheikh; Muhammad Babar Khawar (Biochemical Genetics, 2025)

Self-supervised spatial-spectral transformer with Extreme Learning Machine for Hyperspectral Image Classification - Muhammad Ahmad; Manuel Mazzara; Salvatore Distefano; Adil Mehmood Khan; Xin Wu (International Journal of Remote Sensing, 2025)

Adaptive divergence in Ostrinia furnacalis: Diet-based fitness specification across wild, domestic and hybrid populations - Aleena Alam; Sohail Abbas; Faisal Hafeez; Muhammad Shakeel; Arzlan Abbas; Khalid Ali Khan; Hamed A. Ghramh; Jamin Ali; Adil Tonğa; Rizhao Chen (Crop Protection, 2025)

Assessment of tomato germplasms for Mi-1.2-mediated resistance to Meloidogyne incognita: Integrating in-silico dynamics and bioinformatic approaches - Adil Zahoor; Zeenat Niaz; Muhammad Jabran; Hira Anwar; Amjad Abbas; Abdul Haseeb; Ghulam Mustafa; Sungmi Sun; Seung Hwan Yang; Muhammad Amjad Ali (Physiological and Molecular Plant Pathology, 2025)

A Novel Transfer Learning-Based OFDM Receiver Design for Enhanced Underwater Acoustic Communication - Muhammad Adil; Songzuo Liu; Suleman Mazhar; Ayman Alharbi; Honglu Yan; Muhammad Muzzammil (Journal of Marine Science and Engineering, 2025)
The underwater acoustic (UWA) communication system faces challenges due to environmental factors, extensive multipath spread, and rapidly changing propagation conditions. Deep learning based solutions, especially for orthogonal frequency division multiplexing (OFDM) receivers, have been shown to improve performance. However, the UWA channel characteristics are highly dynamic and depend on the specific underwater conditions. Therefore, these models suffer from model mismatch when deployed in environments different from those used for training, leading to performance degradation and requiring costly, time-consuming retraining. To address these issues, we propose a transfer learning (TL)-based pre-trained model for OFDM based UWA communication. Rather than training separate models for each underwater channel, we aggregate received signals from five distinct WATERMARK channels, across varying signal to noise ratios (SNRs), into a unified dataset. This diverse training set enables the model to generalize across various underwater conditions, ensuring robust performance without extensive retraining. We evaluate the pre-trained model using real-world data from Qingdao Lake in Hangzhou, China, which serves as the target environment. Our experiments show that the model adapts well to these challenging environment, overcoming model mismatch and minimizing computational costs. The proposed TL-based OFDM receiver outperforms traditional methods in terms of bit error rate (BER) and other evaluation metrics. It demonstrates strong adaptability to varying channel conditions. This includes scenarios where training and testing occur on the same channel, under channel mismatch, and with or without fine-tuning on target data. At 10 dB SNR, it achieves an approximately 80% improvement in BER compared to other methods.

Unravelling the role of non-covalent interactions using imidazolium and amino acid based organic salts for efficient CO2 capture: experimental, DFT and COSMO-RS explorations - Hira Karim; Sabahat Sardar; Asad Mumtaz; Anila Tabassum; Muhammad Arfan; Azhar Mahmood; Jean-Marc Leveque; Cecilia Devi Wilfred; Syed Farooq Adil; Mohammad Rafe Hatshan; Mujeeb Khan (Journal of Environmental Chemical Engineering, 2025)

Elicitation of Withania somnifera adventitious roots: in-vitro cultures for enhanced secondary metabolites synthesis - Muhammad Adil; Zohaib Younas; Ilyas Ahmad; Khalid M. Al Rohily; Zia-ur-Rehman Mashwani (Horticulture, Environment, and Biotechnology, 2025)

A Potent Plant-Derived Chitinase: Structural Informatics and Insecticidal Activity against Helicoverpa armigera - Shah Rukh; Ahmed Akrem; Qamar Saeed; Sohaib Mehmood; Nosherwan Adil; Tazeen Rao; Muhammad Nasir; Uzma Ishaq; Aqal Zaman; Najeeb Ullah; Mohibullah Shah (Cell Biochemistry and Biophysics, 2025)

Use of magnetic ionic liquid for selective extraction of proline from wine and honey samples - Muhammad Farooque Lanjwani; Seçkin Fesliyan; Adil Elik; Ayşenur Öztürk Altunay; Mustafa Tuzen (Food Chemistry, 2025)

Molecular prevalence and genetic diversity of Hepatozoon canis in Rhipicephalus sanguineus s.l. and Hyalomma anatolicum infesting dogs - Hafiza Amna Bilal; Madiha Rasool; Arfa Bibi; Hira Muqaddas; Iqra Majeed; Muhammad Farooq; Kasim Sakran Abass; Samir Ibenmoussa; Turki M. Dawoud; Shakir Ullah; Adil Khan; Furhan Iqbal (Comparative Immunology, Microbiology and Infectious Diseases, 2025)

Molecular prevalence and genetic diversity of Toxoplasma gondii in free ranging Asil hen (Gallus gallus domesticus) - Muhammad Naeem; Anees Ur Rehman; Umme Habiba; Zia Ur Rehman; Hira Muqaddas; Amna Aqdas; Turki M. Dawoud; Mohammed Bourhia; Afshan Khan; Adil Khan; Furhan Iqbal (Tropical Animal Health and Production, 2025)

Predictive modeling of fractional plankton-assisted cholera propagation dynamics using Bayesian regularized deep cascaded exogenous neural networks - Adil Sultan; Muhammad Junaid Ali Asif Raja; Chuan-Yu Chang; Chi-Min Shu; Adiqa Kausar Kiani; Muhammad Asif Zahoor Raja (Process Safety and Environmental Protection, 2025)

Unveiling the Potential of Protein-Based Sustainable Antibacterial Materials - Iqra Ghouri; Muslum Demir; Shahid Ali Khan; Muhammad Adil Mansoor; Mudassir Iqbal (Probiotics and Antimicrobial Proteins, 2025)

Deep Q-Learning Based Adaptive MAC Protocol with Collision Avoidance and Efficient Power Control for UWSNs - Wazir Ur Rahman; Qiao Gang; Feng Zhou; Muhammad Tahir; Wasiq Ali; Muhammad Adil; Muhammad Ilyas Khattak (Journal of Marine Science and Engineering, 2025)
Underwater wireless sensor networks (UWSNs) widely used for maritime object detection or for monitoring of oceanic parameters that plays vital role prediction of tsunami to life-cycle of marine species by deploying sensor nodes at random locations. However, the dynamic and unpredictable underwater environment poses significant challenges in communication, including interference, collisions, and energy inefficiency. In changing underwater environment to make routing possible among nodes or/and base station (BS) an adaptive receiver-initiated deep adaptive with power control and collision avoidance MAC (DAWPC-MAC) protocol is proposed to address the challenges of interference, collisions, and energy inefficiency. The proposed framework is based on Deep Q-Learning (DQN) to optimize network performance by enhancing collision avoidance in a varying sensor locations, conserving energy in changing path loss with respect to time and depth and reducing number of relaying nodes to make communication reliable and ensuring synchronization. The dynamic and unpredictable underwater environment, shaped by variations in environmental parameters such as temperature (T) with respect to latitude, longitude, and depth, is carefully considered in the design of the proposed MAC protocol. Sensor nodes are enabled to adaptively schedule wake-up times and efficiently control transmission power to communicate with other sensor nodes and/or courier node plays vital role in routing for data collection and forwarding. DAWPC-MAC ensures energy-efficient and reliable time-sensitive data transmission, improving the packet delivery rati (PDR) by 14%, throughput by over 70%, and utility by more than 60% compared to existing methods like TDTSPC-MAC, DC-MAC, and ALOHA MAC. These enhancements significantly contribute to network longevity and operational efficiency in time-critical underwater applications.

Fostering managers’ hope: A multi-analysis perspective on how green initiatives drive organizational performance - Mohd Adil; Syed Muhammad Fazel-e-Hasan; Hormoz Ahmadi; Mohd Sadiq; Harjit Sekhon; Alireza Amrollahi (Journal of Cleaner Production, 2025)

Enhanced microwave absorption and improved broadband with synergistic effect of nest like self-assembly of CoFe2O4/Co3O4 heterostructured composites - M. Zeeshan Ashfaq; Aamna Ashfaq; Xingxing Cheng; Hongyu Gong; Adil Saleem; Rashid Iqbal; Muhammad Sajjad; Junbin Lu; M. Mamoor; Muhammad K. Majeed (Chemical Engineering Journal, 2025)

An efficient electrodeposition approach for preparing CoMn-hydroxide on nickel foam as high-performance electrodes in aqueous hybrid supercapacitors - Adil Emin; Afei Ding; Muhammad Mateen; Sidra Tul Muntaha; Anand Parkash; Salamat Ali; Qiang Li (Fuel, 2025)

First report of Hepatozoon and Lankesterella spp. infections in wild rodents from Pakistan, and their potential impact on blood parameters and oxidative stress markers in vital organs - Maryam Ijaz; Asmat Ullah Khan; Muhammad Ali; Shakir Ullah; Muhammad Naeem; Samir Ibenmoussa; Turki M. Dawoud; Adil Khan; Mourad Ben Said; Furhan Iqbal (Veterinary Research Communications, 2025)

Exploring environmentally stable and novel genetic factors influencing rice grain shape and yield attributes - Sadia Gull; Zulqarnain Haider; Houwen Gu; Saleem Uddin; Muhammad Qasim; Rana Ahsan Raza Khan; Adil Altaf; Sajid Fiaz; Mona S. Alwahibi; Mohamed S. Elshikh; Rashid Iqbal; Jun Miao; et al. (Euphytica, 2025)

Comet Assay and Micronucleus Test in Circulating Erythrocytes of Ctenopharyngodon idella Exposed to Nickel Oxide Nanoparticles - Jamshid Khan; Nazish Shah; Farmanullah Dawar; Iqra Irfan; Adil Jan; Muhammad Ismail Khan; Muhammad Khisroon (Biological Trace Element Research, 2025)

Intelligent predictive networks for nonlinear oxygen-phytoplankton-zooplankton coupled marine ecosystems under environmental and climatic disruptions - Adil Sultan; Muhammad Junaid Ali Asif Raja; Chuan-Yu Chang; Chi-Min Shu; Muhammad Shoaib; Adiqa Kausar Kiani; Muhammad Asif Zahoor Raja (Process Safety and Environmental Protection, 2025)

Quality assessment of the real-time global ionospheric maps following varying solar dynamics and a severe geomagnetic storm - Muhammad Arqim Adil; Tomasz Hadas; Heng Yang; Manuel Hernandez-Pajares (GPS Solutions, 2025)

The threat of microplastics and microbial degradation potential; a current perspective - Zahid Ullah; Licheng Peng; Adil Farooq Lodhi; Mohib Ullah Kakar; Muhammad Zubair Mehboob; Imran Iqbal (Science of The Total Environment, 2024)

Heterojunction interface engineering enabling high transmittance and record efficiency in Sb2S3 semitransparent solar cell - Muhammad Ishaq; Xuerui Li; Safdar Mehmood; Yi-Ming Zhong; Adil Mansoor; Usman Ali Shah; Shuo Chen; Yuexing Chen; Zhuanghao Zheng; Guangxing Liang (Chemical Engineering Journal, 2024)

MicroRNA expression profiling of ovine epithelial cells stimulated with the Staphylococcus aureus in vitro - Ghulam Asghar Sajid; Muhammad Jasim Uddin; Saif Adil Abbood Al-Janabi; Abdiaziz Nur Ibrahim; Mehmet Ulas Cinar (Mammalian Genome, 2024)

Microfluidic devices for the isolation and label-free identification of circulating tumor cells - Muhammad Anwar; Nuno M. Reis; Chi Zhang; Adil Khan; Kashif Ali Kalhoro; Atiq Ur Rehman; Yanke Zhang; Zhengchun Liu (Chemical Engineering Journal, 2024)

Assessment of natural radioactivity levels in rice samples and their implications for radiological protection - Hannan Younis; Mian Mateen Ullah; Muhammad Adil Khan; Farooq Ahmad; Umair Azeem; Muhammad Waseem; Khurram Mehboob; Muhammad Ajaz; Wazir Muhammad (Isotopes in Environmental and Health Studies, 2024)

Zinc and methyl jasmonate improve sugar beet tolerance to high boron stress by enhanced leaf photochemical performance - Jialu Huo; Xiaoyu Zhao; Baiquan Song; Muhammad Faheem Adil; Shafaque Sehar; Xilong Liang; Jiaxin Li; Muhammad Ishfaq; Shangxuan Liu; Songlin Yang (Journal of Environmental Management, 2024)

Antioxidant dimension and potential as bacterial growth inhibitors in crude extracts of two Artemisia species (Artemisia indica Willd. and Artemisia maritima L.) from Gilgit-Baltistan region, Pakistan - Hassam Rasheed; Adil Hussain; Muhammad Aslam Khan; Mujtaba Hassan; Syed Ali Imran Bokhari (Vegetos, 2024)

A new empirical correlation of MMP prediction for oil – impure CO2 systems - Haiyang Yu; Jiayi Feng; Huake Zeng; Qichao Xie; Jiawei Wang; Jiabang Song; Muhammad Adil Abdullah; Yang Wang; Yiwen Wang; Jun Lu (Fuel, 2024)

Preparation, characterization and functional evaluation of soy protein isolate-peach gum conjugates prepared by wet heating Maillard reaction - Arif Hussain; Muhammad Hussain; Waqas Ashraf; Aiman Karim; Sahibzada Muhammad Aqeel; Adil Khan; Asif Hussain; Salman Khan; Zhang Lianfu (Food Research International, 2024)

Drivers of municipal water security and vulnerability in Pakistan: A case study of Mardan, Khyber Pakhtunkhwa - Kamran; Junaid Aziz Khan; Fasiha Safdar; Umer Khayyam; Iftikhar Hussain Adil; Abdul Waheed; Muhammad Fahim Khokhar (Groundwater for Sustainable Development, 2024)

Tree-ring based summer temperature variability since 1790 CE in the Hindu Kush region of northern Pakistan - Fayaz Asad; Muhammad Adil; Sabrina Shahid; Nasrullah Khan; Ru Huang; Haifeng Zhu (International Journal of Biometeorology, 2024)

Seismo-ionospheric precursory detection using hybrid Bayesian-LSTM network model with uncertainty-boundaries and anomaly-intensity - Mohd Saqib; Erman Şentürk; Muhammad Arqim Adil; Mohamed Freeshah (Advances in Space Research, 2024)

Enhancing wheat performance through phosphorus and zinc management strategies under varied irrigation regimes - Abdul Latif Jan; Amanullah; Adil Mihoub; Muhammad Fawad; Muhammad Farhan Saeed; Imad Khan; Emanuele Radicetti; Aftab Jamal (Environment, Development and Sustainability, 2024)

Assessment of flexural performance of reinforced mud sandwich panels: experimental and numerical modeling approach - Muhammad Waleed Sarwar; Mohammad Adil; Zahid Ullah; Muhammad Ali Sikandar; Muhammad Tariq Bashir; Zafar Baloch; Syed Azmat Ali Shah (Innovative Infrastructure Solutions, 2024)

Progress, challenges, and prospects of MOF-based adsorbents for phosphate recovery from wastewater - Muhammad Naveed Afridi; Sawaira Adil; Battuya Byambaa; Muhammad Sohail; Aziz-Ur-Rahim Bacha; Jingwen Wang; Chaolin Li (Journal of Water Process Engineering, 2024)

Insights into the alleviation of cadmium toxicity in rice by nano-zinc and Serendipita indica: Modulation of stress-responsive gene expression and antioxidant defense system activation - Muhammad Faheem Adil; Shafaque Sehar; Zhengxin Ma; Khajista Tahira; Syed Muhammad Hassan Askri; Mohamed A. El-Sheikh; Aqeel Ahmad; Fanrui Zhou; Ping Zhao; Imran Haider Shamsi (Environmental Pollution, 2024)

Morpho-Physiological and Enzymatic Responses of Zinnia (Zinnia elegans L.) to Different Metal Hoarded Wastewaters - Muhammad Ahsan; Adnan Younis; Muhammad Raheel; Imran Khalid; Hafiz Tassawar Abbas; Waqas Ashraf; Adil Mihoub; Emanuele Radicetti; Muhammad Farhan Saeed; Sajjad Ali; Mohammad Valipour; Aftab Jamal (Journal of Soil Science and Plant Nutrition, 2024)

Combined Effect of Biochar and Plant Growth-Promoting Rhizbacteria on Physiological Responses of Canola (Brassica napus L.) Subjected to Drought Stress - Gul-Lalay; Sami Ullah; Sikandar Shah; Aftab Jamal; Muhammad Farhan Saeed; Adil Mihoub; Adil Zia; Iftikhar Ahmed; Mahmoud F. Seleiman; Roberto Mancinelli; Emanuele Radicetti (Journal of Plant Growth Regulation, 2024)
Biochar (BC) and plant growth-promoting microbes (PGPR) could represent a suitable agronomical strategy to mitigate the impacts of drought in arid agro-environmental conditions. However, there is currently little understanding of the synergistic benefit of combining BC and PGPR to increase drought tolerance in oilseeds. In this study, the physiological response of two water-stressed canola ( Brassica napus L.) plants subjected to the application of BC obtained from waste wood of Morus alba applied solely or in combination with PGPR strains ( Pseudomonas sp.) was evaluated. The experiment consists of two genotypes and nine treatments [(C-Control, T1-15 days drought (15DD), T2-30 days drought (30DD), T3-15 days of drought + PG (15DD + PG), T4-30 days of drought + PG (30DD + PG), T5-15 days drought + biochar (15DD + BC), T6-30 days drought + biochar (30DD + BC), T7-15 days drought + biochar + PG (15DD + BC + PG), T8-30 days drought + biochar + PG (30DD + BC + PG)]. Drought stress decreased emergence energy (EE), leaf area index (LAI), leaf area ratio (LAR), root shoot ratio (RSR), moisture content of leaves (MCL), percent moisture content (%MC), moisture content of shoot (MCS) and moisture content of root (MCR), and relative water content (RWC) in both varieties of Brassica napus L., which in contrast, it is increased by the collective application of both biochar and PGPR. In both varieties, N, P, K, Mg, and Ca concentrations were highest in all the biochar and PGPRs separate and combined treatments, while lowest in 15 and 30 days drought treatments. Osmolyte contents like Glycine betaine (GB) and sugar remarkably increased in the stress condition and then reduced due to the synergistic application of biochar and PGPR. Drought stress has a repressive effect on the antioxidant enzymatic system like Peroxidase (POD), Superoxide dismutase (SOD), and glutathione reductase (GR) as well as total flavonoids, phenolics, and protein content. The antioxidant enzymes and phenolic compounds were dramatically increased by the combined action of biochar and PGPRs. A significant increase in EE, LAR, RSR, and RWC under 15 and 30 days drought conditions, evidently highlighting the synergistic effect of BC and PGPR. The results conclude a substantial and positive effect of the combined use of BC and PGPR strains on canola's response to induced drought stress, by regulating the physiological, biochemical, and agronomic traits of the plants. Graphical Abstract

Multi-omics tools for understanding Trichoderma-plant symbiosis: biotechnological developments and future directions - Nur Syafikah Abdullah; Febri Doni; Muhammad Adil Awal; Muhamad Shakirin Mispan; Mohd Zuwairi Saiman; Yusmin Mohd-Yusuf; Nurul Shamsinah Mohd Suhaimi (Symbiosis, 2024)

Bioactive compounds isolated from Solanum nigrum remarkably inhibit cancerous activity in cancer cell lines - Aisha Nawaz; Adil Jamal; Amina Arif; Shumaila Kiran; Muhammad Naveed Shahid; Shafia Arshad; Zeeshan Shamim (South African Journal of Botany, 2024)

Cadmium Stress Alleviation: Interplay of Micronutrients and Enzymatic/Non-enzymatic Species in Maize by Organic and Inorganic Amendments - Sehar Razzaq; Beibei Zhou; Muhammad Adil; Zakir Ullah; Hongchao Guo; Muhammad Zia-Ur-Rehman; Chen Xiaopeng; Li Wen Qian; Heli Lu (Water, Air, & Soil Pollution, 2024)

Impact of heavy metals on aquatic life and human health: a case study of River Ravi Pakistan - Muhammad Irfan Ahamad; Zijie Yao; Liang Ren; Cheng Zhang; Tingting Li; Heli Lu; Muhammad Sajid Mehmood; Adnanul Rehman; Muhammad Adil; Siqi Lu; Wanfu Feng (Frontiers in Marine Science, 2024)
Heavy-metal contamination in river and ocean is a critical environmental issue that endangers marine ecosystems and human health. Therefore, conducting extensive research to devise effective mitigation measures is imperative. Sediment samples were taken randomly throughout the study area. Analysis was done to determine the presence of different metals, including arsenic, cadmium, chromium, nickel, copper, zinc, lead, and manganese. The assessment of different pollution levels was done by using various pollution indicators including “geo-accumulation index (Igeo), contamination factor (CF), enrichment factor (EF)” for accuracy. The Igeo measurement for Cd indicated varying pollution, ranging from moderate to significantly polluted, while Mn revealed no contamination. Elements such as Ni, Cr, Cu, and Zn showed a moderate level of contamination. The contamination factor values exhibited a range of 0.436 (Pb) to 7.637 (Cd), with average values spanning from 0.9176 (Mn) to 4.9714 (Cd), suggesting significant regional variation. EF exhibits a pattern of contamination comparable to that of Igeo. The noncarcinogenic risk associated with exposure to Cd and As exceeded the higher limit (HI > 1) for children and adults. Furthermore, the carcinogenic risk presented by pollutants such as copper (Cu), arsenic (As), nickel (Ni), cadmium (Cd), and chromium (Cr) was found to exceed the limits in children. In adults, only arsenic (As) and copper (Cu) were shown to represent a higher risk of cancer than the limit of 10 −4 . The PCA analysis revealed that two (PCs) accounted for more than 65% of the total variance in the River Ravi, as determined by eigenvalues greater than 1. This study underscores the importance of the ongoing monitoring and management of heavy-metal pollution to ensure sustainable marine ecosystem development and public health protection.

Sensitive method for determination of benzoic acid in beverages and food samples using air–assisted hydrophobic deep eutectic solvent-based dispersive liquid-liquid microextraction - Nail Altunay; Muhammad Farooque Lanjwani; Hameed Ul Haq; Mustafa Tuzen; Adil Elik (Sustainable Chemistry and Pharmacy, 2024)

Hydrogen from sewage sludge: Production methods, influencing factors, challenges, and prospects - Usman Khan; Muhammad Bilal; Hossain Md. Adil; Nnabodo Darlington; Ahsan Khan; Nouman Khan; I. Ihsanullah (Science of The Total Environment, 2024)

Nutrient and mycoremediation of a global menace ‘arsenic’: exploring the prospects of phosphorus and Serendipita indica-based mitigation strategies in rice and other crops - Shafaque Sehar; Muhammad Faheem Adil; Syed Muhammad Hassan Askri; Elvis Dennis; Mohammad Faizan; Ping Zhao; Fanrui Zhou; Imran Haider Shamsi (Plant Cell Reports, 2024)

Leading report of molecular prevalence of tick borne Anaplasma marginale and Theileria ovis in yaks (Bos grunniens) from Pakistan - Muqaddas Nawaz; Rehmat Ullah; Zia Ur Rehman; Muhammad Naeem; Afshan Khan; Mohammed Bourhia; Muhammad Mudassir Sohail; Takbir Ali; Adil Khan; Tanveer Hussain; Furhan Iqbal (Archives of Microbiology, 2024)

The challenges and opportunities of localizing the sustainable development goals in Canadian cities – a subsidiarity check - Muhammad Adil Rauf; Cameron McCordic; Bruce Frayne (Environment, Development and Sustainability, 2024)

Variations in rhizosphere soil dominant and pathogenic flora improve boron-efficient Beta vulgaris L. yield under boron deficit - Shangxuan Liu; Baiquan Song; Shafaque Sehar; Muhammad Faheem Adil; Xiaochen Lin; Jialu Huo; Xiaoyu Zhao; Muhammad Riaz (Journal of Cleaner Production, 2024)

Molecular prevalence of vector borne bacterial pathogens in the blood samples of wild rodent species trapped from Saudi Arabia - Abdul Ghafar; Samia Q. Alghamdi; Abdullah D. Alanazi; Syed Muhammad Zukhruf Qousain; Maryam Ijaz; Muhammad Naeem; Muhammad Ali; Hira Muqaddas; Adil Khan; Furhan Iqbal (Comparative Immunology, Microbiology and Infectious Diseases, 2024)

A cyclone formation, eastward plume drag, ion-hydration process, and the consequent ionospheric changes following the 2022 Hunga Tonga-Hunga Ha'apai volcanic eruption - Mohamed Freeshah; Muhammad Arqim Adil; Erman Şentürk; Xiaohong Zhang; Xiaodong Ren; Hang Liu; Nahed Osama (Advances in Space Research, 2024)

Theoretical and experimental explored tailored hybrid H+/O2– ions conduction: Bridged for high performance fuel cell and water electrolysis - Zuhra Tayyab; Sajid Rauf; Muhammad Bilal Hanif; Hafiz Imran Ahmad Qazi; Naveed Mushtaq; Martin Motola; Sining Yun; Chen Xia; Dmitry A. Medvedev; Muhammad Imran Asghar; Abdullah N. Alodhayb; Arshad Hussain; et al. (Chemical Engineering Journal, 2024)

Comparative taxonomy and evolutionary significance of foliar epidermis in Jasminum L. (Oleaceae) based on light and scanning electron microscopy - Naeem Akhtar; Muhammad Q. Hayat; Umer Habib; Muhammad A. Khan; Saad I. Malik; Hina Hafeez; Adil Hussain; Azhar Hussain; Daniel Potter (Flora, 2024)

Synergistic effect of CuO and Sr doped g-C3N4 for CO2 photoreduction into hydrocarbon fuels - Adil Raza; Azhar Ali Haidry; Zhengjun Yao; Muhammad Farooq Saleem; Asma A. Alothman; Saikh Mohammad (Chemical Engineering Journal, 2024)

Quantifying future water-saving potential under climate change and groundwater recharge scenarios in Lower Chenab Canal, Indus River Basin - Muhammad Shafeeque; Mohsin Hafeez; Abid Sarwar; Arfan Arshad; Tahira Khurshid; Muhammad Irfan Asim; Shoaib Ali; Adil Dilawar (Theoretical and Applied Climatology, 2024)
Quantifying water-saving potential (WSP) is crucial for sustainable water resource management in canal command areas and river basins. Previous studies have partially or fully ignored the importance of groundwater in WSP assessments, particularly in irrigated areas. This study is aimed at quantifying WSP in the Lower Chenab Canal (LCC) command area of the Indus River Basin, Pakistan, under various scenarios of future climate change and groundwater recharge. These quantifications are conducted using an empirical model based on the Budyko theory. The model was forced using observed, remote sensing, and CMIP6 future climate data for two Shared Socioeconomic Pathways (SSP245 and SSP585) and their ensembles (cold-dry, cold-wet, warm-dry, and warm-wet) for possible futures. The results showed that the average WSP in the LCC command area was 466 ± 48 mm/year during the historical period (2001–2020). The WSP is projected to decrease by – 68 ± 3% under the warm-dry ensemble scenario (SSP245 and SSP585) and – 48 ± 13% under the ensembled cold-wet scenario by 2100. The results also demonstrated that WSP could be increased by up to 70 ± 9% by artificially recharging 20% of the abstracted groundwater per year in the LCC command area by the late twenty-first century. Our findings highlight the importance of adopting artificial groundwater recharge to enhance the WSP and sustainably manage water resources in the LCC command area. Policymakers should consider these findings when deciding on water resource management in the Indus River Basin.

A practical tool for structural design optimization of steel frames: development and application for parametric analysis - Umair Ali; Rizwan Azam; Mansoor Shakeel; Muhammad Adil; Muhammad Rizwan Riaz (Innovative Infrastructure Solutions, 2024)

Production, purification, and characterization of p-diphenol oxidase (PDO) enzyme from lignolytic fungal isolate Schizophyllum commune MF-O5 - Muhammad Faheem; Syed Ali Imran Bokhari; Muhammad Arshad Malik; Bashir Ahmad; Muhammad Riaz; Nafeesa Zahid; Adil Hussain; Abdul Ghani; Hanif Ullah; Waseem Shah; Rashid Mehmood; Khurshid Ahmad; et al. (Folia Microbiologica, 2023)

Response of the rhizospheric soil microbial community of sugar beet to nitrogen application: A case of black soil in Northeast China - Xiaochen Lin; Baiquan Song; Muhammad Faheem Adil; Milan Kumar Lal; Qiue Jia; Qiuhong Wang; Xin Song (Applied Soil Ecology, 2023)

Casting shadows on natural resource commodity markets: Unraveling the quantile dilemma of gold and crude oil prices - Muhammad Luqman; Adil Mugheri; Najid Ahmad; Ugur Soytas (Resources Policy, 2023)

Eliciting the Response of Rhizospheric Soil Microbial Community Structure to Zinc Amendment: A Case Study of Sugar Beet Cultivation in Black Soil - Qiue Jia; Baiquan Song; Jialu Huo; Xin Song; Yan Wang; Muhammad Faheem Adil; Muhammad Riaz; Milan Kumar Lal; Hayssam M. Ali (Sugar Tech, 2023)

A systematic review of physiological signals based driver drowsiness detection systems - Adil Ali Saleem; Hafeez Ur Rehman Siddiqui; Muhammad Amjad Raza; Furqan Rustam; Sandra Dudley; Imran Ashraf (Cognitive Neurodynamics, 2023)

Correction to: Long-term spatio-temporal trends in atmospheric aerosols and trace gases over Pakistan using remote sensing - Muhammad Adil Javed; Usman Mehmood; Salman Tariq; Zia ul Haq (Acta Geophysica, 2023)

Stabilizing anionic redox in Mn-rich P2-type layered oxide material by Mg substitution - Sidra Jamil; Yiming Feng; Muhammad Fasehullah; Ghulam Ali; Bing Wu; Yu-Jie Guo; Bushra Jabar; Adil Mansoor; Yu-Bin Niu; Maowen Xu (Chemical Engineering Journal, 2023)

Effect of heterologous platelet-rich plasma on liver and modulation of glucose metabolism and Wnt signalling pathways in diabetic mice - Amin Arif; Adil Farooq; Muddasir Hassan Abbasi; Muhammad Babar Khawar; Tasleem Akhtar; Humaira Allay Ali; Mehreen Anjum; Rabia Mehmood; Tayyaba Saleem; Nadeem Sheikh (Molecular Biology Reports, 2023)

Enhancing accuracy of extreme learning machine in predicting river flow using improved reptile search algorithm - Rana Muhammad Adnan; Reham R. Mostafa; Hong-Liang Dai; Salim Heddam; Adil Masood; Ozgur Kisi (Stochastic Environmental Research and Risk Assessment, 2023)

Diversity in Elemental Content in Selected Artemisia L. (Asteraceae) Species from Gilgit-Baltistan Region of Pakistan Based on Inductively Coupled Plasma Atomic Emission Spectrophotometry (ICP-AES) - Adil Hussain; Muhammad Sajid; Daniel Potter; Hassam Rasheed; Mujtaba Hassan; Naeem Akhtar; Bashir Ahmad; Syed Ali Imran Bokhari (Biological Trace Element Research, 2023)

Long-term spatio-temporal trends in atmospheric aerosols and trace gases over Pakistan using remote sensing - Muhammad Adil Javed; Usman Mehmood; Salman Tariq; Zia ul Haq (Acta Geophysica, 2023)

Zinc amendment increases the yield and industrial quality of Beta vulgaris L. cultivated in Northeast China - Xiaoyu Zhao; Baiquan Song; Muhammad Ishfaq; Muhammad Faheem Adil; Milan Kumar Lal; Zhenzhen Wu; Qiue Jia; Wengong Huang (Field Crops Research, 2023)

Construction of Satellite Genetic System for Robust and Versatile Inter-species Gene Function Analyses in Viola - Donghyeon Kim; Jong-Yoon Park; Jihyun Won; Adil Muhammad; Ju Young Bang; Seula Lee; Youbong Hyun (Journal of Plant Biology, 2023)

Long-term ion hydration process and lithosphere-atmosphere coupling following the 2021 Fagradalsfjall volcanic eruption using remotely sensed data - Erman Şentürk; Muhammad Arqim Adil; Mustafa Toker; Muzaffer Can Iban; Özer Akyürek (Advances in Space Research, 2023)

Detection and quantification of aflatoxins in spices stored in different food packaging materials - Muhammad Abrar; Samreen Ahsan; Muhmmad Nadeem; Atif Liaqat; Muhmmad Farhan Jahangir Chughtai; Muhammad Adil Farooq; Tariq Mehmood; Adnan Khaliq; Ayesha Siddiqa (Journal of Stored Products Research, 2023)

Industrial scale thin-film composite membrane modules for salinity-gradient energy harvesting through pressure retarded osmosis - Jiun Hui Low; Junyou Zhang; Weikun Paul Li; Tianshi Yang; Chun Feng Wan; Farhana Esa; Marn Soon Qua; Karikalan Mottaiyan; Suresh Murugan; Muhammad Aiman; Adil Dhalla; Tai-Shung Chung; et al. (Desalination, 2023)

Polyetherimide membrane with tunable porous morphology for safe lithium metal-based batteries - Arshad Hussain; Andleeb Mehmood; Adil Saleem; Muhammad K. Majeed; Waseem Raza; Rashid Iqbal; Sajid Rauf; Ali Saad; Yonggui Deng; Geng Luo; Kai Zong; Liu Wei; et al. (Chemical Engineering Journal, 2023)

The optimum cooking time: A possible key index for predicting the deterioration of fresh white-salted noodle - Qin Guo; Yun-ting Li; Jia-hui Cai; Cheng-wan Ren; Muhammad Adil Farooq; Bin Xu (Journal of Cereal Science, 2023)

Electrically conductive Pt-MOFs for acidic oxygen reduction: Optimized performance via altering conjugated ligands - Rashid Iqbal; Sajjad Ali; Adil Saleem; Muhammad K. Majeed; Arshad Hussain; Sajid Rauf; Abdul Rehman Akbar; Hu Xu; Liang Qiao; Wei Zhao (Chemical Engineering Journal, 2023)

GNSS atmosphere seismology for equatorial earthquakes: a case study from Central America - Muhammad Arqim Adil; Sergey Alexander Pulinets; Erman Şentürk; Abdur Rafeh Abbasi; Pavel Budnikov (GPS Solutions, 2022)

Energy, exergy, economic, environmental, energoeconomic, exergoeconomic, and enviroeconomic (7E) analyses of wind farms: a case study of Pakistan - Muhammad Uzair Yousuf; Muhammad Adil Abbasi; Muhammad Kashif; Muhammad Umair (Environmental Science and Pollution Research, 2022)

Bacterial Redox Cycling of Manganese in Calcareous Soil Enhances the Nutrients Bioavailability to Wheat - Saba Babar; Ghulam Jilani; Adil Mihoub; Aftab Jamal; Iftikhar Ahmad; Arshad Nawaz Chaudhary; Muhammad Farhan Saeed; Tajwar Alam (Journal of Soil Science and Plant Nutrition, 2022)

Citric Acid (CA)–Modified Biochar Improved Available Phosphorus Concentration and Its Half-Life in a P-Fertilized Calcareous Sandy Soil - Adil Mihoub; Abu El-Eyuoon Abu Zied Amin; Hamid Reza Motaghian; Muhammad Farhan Saeed; Asif Naeem (Journal of Soil Science and Plant Nutrition, 2022)

Comparisons of autoregressive integrated moving average (ARIMA) and long short term memory (LSTM) network models for ionospheric anomalies detection: a study on Haiti (Mw = 7.0) earthquake - Mohd Saqib; Erman Şentürk; Sanjeev Anand Sahu; Muhammad Arqim Adil (Acta Geodaetica et Geophysica, 2022)

Anti-hepatitis C virus and synergistic potential of Syzgium cumine a bioassay guided screening in liver-infected hepatocytes - Sana Riaz; Hira Tiwana; Muhammad Adil; Khaver Ali; Tariq Javed (Archives of Microbiology, 2022)

Fully Automatic Registration Methods for Chest X-Ray Images - Yu-Ching Lee; Muhammad Adil Khalil; Jui-Huan Lee; Abdan Syakura; Yi-Fang Ding; Ching-Wei Wang (Journal of Medical and Biological Engineering, 2021)

A Lithosphere–Atmosphere–Ionosphere Coupling Phenomenon Observed Before M 7.7 Jamaica Earthquake - Muhammad Arqim Adil; Erman Şentürk; Sergey Alexander Pulinets; Christine Amory-Mazaudier (Pure and Applied Geophysics, 2021)

Air pollution and child health: the impact of brick kiln pollution on children's cognitive abilities and physical health in Pakistan - Muhammad Nasir; Faiz Ur Rehman; Shabana Kishwar; Saima Bashir; Muhammad Adil (Environment, Development and Sustainability, 2021)

Ionospheric anomalies detection using autoregressive integrated moving average (ARIMA) model as an earthquake precursor - Mohd Saqib; Erman Şentürk; Sanjeev Anand Sahu; Muhammad Arqim Adil (Acta Geophysica, 2021)

RP-HPLC-based phytochemical analysis and diverse pharmacological evaluation of Quercus floribunda Lindl. ex A. Camus nuts extracts - Madiha Ahmed; Muhammad Adil; Ihsan-ul- Haq; Muhammad Khalid Tipu; Muhammad Qasim; Bilquees Gul (Natural Product Research, 2021)

Correction to: Anomaly Classification for Earthquake Prediction in Radon Time Series Data Using Stacking and Automatic Anomaly Indication Function - Adil Aslam Mir; Fatih Vehbi Çelebi; Muhammad Rafique; M. R. I. Faruque; Mayeen Uddin Khandaker; Kimberlee Jane Kearfott; Pervaiz Ahmad (Pure and Applied Geophysics, 2021)

A real-time camera-based adaptive breathing monitoring system - Yu-Ching Lee; Abdan Syakura; Muhammad Adil Khalil; Ching-Ho Wu; Yi-Fang Ding; Ching-Wei Wang (Medical & Biological Engineering & Computing, 2021)

Anomaly Classification for Earthquake Prediction in Radon Time Series Data Using Stacking and Automatic Anomaly Indication Function - Adil Aslam Mir; Fatih Vehbi Çelebi; Muhammad Rafique; M. R. I. Faruque; Mayeen Uddin Khandaker; Kimberlee Jane Kearfott; Pervaiz Ahmad (Pure and Applied Geophysics, 2021)

Alkaline lipase production by novel meso-tolerant psychrophilic Exiguobacterium sp. strain (AMBL-20) isolated from glacier of northeastern Pakistan - Muhammad Talha Yasin; Yasir Ali; Khurshid Ahmad; Abdul Ghani; Kinza Amanat; Muhammad Mudassir Basheir; Muhammad Faheem; Saddam Hussain; Bashir Ahmad; Adil Hussain; Syed Ali Imran Bokhari (Archives of Microbiology, 2021)

Urban infrastructure finance and its relationship to land markets, land development, and sustainability: a case study of the city of Islamabad, Pakistan - Muhammad Adil Rauf; Olaf Weber (Environment, Development and Sustainability, 2021)

Phytosynthesis of poly (ethylene glycol) methacrylate-hybridized gold nanoparticles from C. tuberculata: their structural characterization and potential for in vitro growth in banana - Natasha Anwar; Jan Wahid; Jalal Uddin; Abbas Khan; Mohib Shah; Syed Adil Shah; Fazle Subhan; Mubarak Ali Khan; Kazim Ali; Mamoona Rauf; Muhammad Arif (In Vitro Cellular & Developmental Biology - Plant, 2021)

The MYB transcription factor Baymax1 plays a critical role in rice male fertility - Xiao-Jiao Xiang; Lian-Ping Sun; Ping Yu; Zheng-Fu Yang; Pei-Pei Zhang; Ying-Xin Zhang; Wei-Xun Wu; Dai-Bo Chen; Xiao-Deng Zhan; Riaz-Muhammad Khan; Adil Abbas; Shi-Hua Cheng; et al. (Theoretical and Applied Genetics, 2021)

Artemisia chamaemelifolia Vill: a rare species of genus Artemisia (Asteraceae-Anthemideae) now present in the northeast (Gilgit-Baltistan) region of Pakistan - Adil Hussain; Muhammad Qasim Hayat; Syed Ali Imran Bokhari (Biologia, 2021)

Screening of Lipase-Producing Bacteria and Optimization of Lipase-Mediated Biodiesel Production from Jatropha curcas Seed Oil Using Whole Cell Approach - Abdul Haq; Sana Adeel; Alam Khan; Qurrat ul ain Rana; Muhammad Adil Nawaz Khan; Muhammad Rafiq; Muhammad Ishfaq; Samiullah Khan; Aamer Ali Shah; Fariha Hasan; Safia Ahmed; Malik Badshah (BioEnergy Research, 2020)

The potential of Allium sativum and Cannabis sativa extracts for anti-tick activities against Rhipicephalus (Boophilus) microplus - Nasreen Nasreen; Sadaf Niaz; Adil Khan; Muhammad Arfan Zaman; Sultan Ayaz; Huma Naeem; Nasrullah Khan; Abdallah M. Elgorban (Experimental and Applied Acarology, 2020)

Isolation and functional characterization of an Ethylene Response Factor (RhERF092) from rose (Rosa hybrida) - Muhammad Ali Khan; Muhammad Imtiaz; Adil Hussain; Fazal Jalal; Sikandar Hayat; Sayed Hussain; Fazal Said; Mehboob Alam; Rabia Amir (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Identification of QTLs associated with p-coumaric acid and ferulic acid in barley - Zhigang Han; Huaizhou Gao; Lingzheng Ye; Muhammad Faheem Adil; Muhammad Ahsan; Guoping Zhang (Euphytica, 2019)

Acaricidal efficacy of Calotropis procera (Asclepiadaceae) and Taraxacum officinale (Asteraceae) against Rhipicephalus microplus from Mardan, Pakistan - Adil Khan; Nasreen Nasreen; Sadaf Niaz; Sultan Ayaz; Huma Naeem; Ijaz Muhammad; Fazal Said; Robert D. Mitchell; Adalberto A. Pérez de León; Snehil Gupta; Sachin Kumar (Experimental and Applied Acarology, 2019)

Evaluation of Abuse-Deterrent Characteristics of Tablets Prepared via Hot-Melt Extrusion - Xiaoming Xu; Akhtar Siddiqui; Charudharshini Srinivasan; Adil Mohammad; Ziyaur Rahman; Maxwell Korang-Yeboah; Xin Feng; Mansoor Khan; Muhammad Ashraf (AAPS PharmSciTech, 2019)

Effect of explant type and plant growth regulators on callus induction, growth and secondary metabolites production in Cnidium officinale Makino - Muhammad Adil; Xiuxia Ren; Dong Il Kang; Luc The Thi; Byoung Ryong Jeong (Molecular Biology Reports, 2018)

Role of sorption energy and chemisorption in batch methylene blue and Cu2+ adsorption by novel thuja cone carbon in binary component system: linear and nonlinear modeling - Saeed Rehman; Adnan Adil; Ahsan Jabbar Shaikh; Jehanzeb Ali Shah; Muhammad Arshad; Muhammad Arif Ali; Muhammad Bilal (Environmental Science and Pollution Research, 2018)

Classification of rocks radionuclide data using machine learning techniques - Abdul Razzaq Khan; Adil Aslam Mir; Sharjil Saeed; Muhammad Rafique; Khawaja M. Asim; Talat Iqbal; Abdul Jabbar; Saeed Ur Rahman (Acta Geophysica, 2018)

Profile and Time-Scale Dynamics of Differentially Expressed Genes in Transcriptome of Populus davidiana Under Drought Stress - Bong-Gyu Mun; Adil Hussain; Eung-Jun Park; Sang-Uk Lee; Arti Sharma; Qari Muhammad Imran; Ki-Hong Jung; Byung-Wook Yun (Plant Molecular Biology Reporter, 2017)

3D graphene-based nanostructured materials as sorbents for cleaning oil spills and for the removal of dyes and miscellaneous pollutants present in water - Muhammad Adil Riaz; Gordon McKay; Junaid Saleem (Environmental Science and Pollution Research, 2017)

Comparative study of performance of real-time satellite-derived rainfall in Swat Catchment - Muhammad Umar; Adil Latif; Syed Amer Mahmood (Arabian Journal of Geosciences, 2017)

Interactive effects of melatonin and light on growth parameters and biochemical markers in adventitious roots of Withania somnifera L. - Muhammad Adil; Bilal Haider Abbasi; Tariq Khan (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Estimation of Toxic Metals in Scalp Hair Samples of Chronic Kidney Patients - Tasneem Gul Kazi; Nusrat Jalbani; Naveed Kazi; Muhammad Balal Arain; Muhammad Khan Jamali; Hassan Imran Afridi; Ghulam Abbas Kandhro; Raja Adil Sarfraz; Abdul Qadir Shah; Rehana Ansari (Biological Trace Element Research, 2009)